Experimental investigation and modeling on the dissociation conditions of methane hydrate in clayey silt cores. Issue 9 (10th June 2022) - Yu, Changhong; Sun, Baojiang; Yang, Tangyang; Wang, Zhiyuan; Gao, Yonghai; Chen, Litao
Abstract: As the majority of global natural gas hydrate reserve, the dissociation conditions of hydrate in clayey silts are of great significance for its efficient production. In this work, the dissociation conditions of methane hydrate in clayey silt cores were experimentally measured by step‐heating method at the temperature range of 280.76–289.55 K and pressure range of 8.11–15.03 MPa, respectively. Various cores including quartz powder, montmorillonite, and South China Sea sediments at the water content range of 20%–33% were used for investigation. The results showed that the dissociation temperatures of methane hydrate in clayey silt cores depressed compared to bulk hydrate. The grain size, salinity, and lithology of clayey silt cores significantly affect the dissociation conditions of hydrate. In comparison to grain size, salinity, and lithology had a more significant influence on the equilibrium temperature depression. The dissociation temperature depression of methane hydrate was considered as a consequence of the water activity depression which is caused by the effect of capillary, salt, or clay. A water activity meter was used to measure the water activity in clayey silt cores. The influence of salt component and mineral characteristics on the water activity was investigated. By combining the measured water activity data with the Chen‐Guo model, a novel water activity measurement (WAM) method for the hydrate dissociation conditions prediction was proposed. With the maximum deviation less than 12%, the predicted results are in good agreement with the experimental data. It demonstrated that the WAM method could effectively predict the dissociation conditions of methane hydrate in clayey silts with convenience and accuracy.